Minimal similarity in songs suggests limited exchange between humpback whales (Megaptera novaeangliae) in the southern Indian Ocean. - Murray, A.; Salvatore, C.; McCauley, Robert; Jenner, C.; Razafindrakoto, Y.; Coughran, D.; McKay, Shannon; Rosenbaum, H. (Society for Marine Mammology, 2012)
Comparing humpback whale song from different breeding assemblages can reveal similarities in song due to acoustically interacting males, and therefore indirectly test whether males from different breeding sites are mixing. Northern Hemisphere song comparisons illustrated that whales within ocean basins share similar songs and are subpopulations within a larger population, whereas whales in different ocean basins are isolated populations and therefore do not share songs. During the 2006 breeding season, recordings were collected in Madagascar and Western Australia, and were compared visually plus aurally. Both regions shared one theme, whereas each region had four and six private themes, respectively. This study had a substantially low number of shared themes. The co-occurrence of one theme was interpreted as an indication of limited exchange between these breeding assemblages, and we speculate that limited song similarity is due to inter-oceanic interactions. Male(s) from an Indian Ocean breeding group could be exposed to novel song when they geographically overlap, and acoustically interact, with males from a different ocean basin. Novel song could induce rapid temporal changes as new song content is incorporated, thereby minimizing song similarities between that breeding group and other Indian Ocean breeding groups that were not exposed to the novel song.